Hybrid transanal and total mesorectal excision after transanal endoscopic microsurgery for unfavourable early rectal cancer: a report of two cases - Samalavičius, Narimantas E.; Dulskas, Audrius; Petrulis, Kęstutis; Kilius, Alfredas; Tikuišis, Renatas; Lunevičius, Raimundas (Acta medica Lituanica, 2017)
Completion total mesorectal excision (TME) is a rare but complex procedure after transanal endoscopic microsurgery for early rectal cancer with unfavourable final histology. Two cases are reported when completion TME was performed after upfront transanal partial mesorectal dissection. Intact non-perforated TME specimens with negative and adequate distal and circumferential margins were created. The quality of both total mesorectal excisions was complete and distal margins were sufficient. We believe that our technique might be a way of approaching completion TME after TEM, especially in cases of low rectal cancer.
Keywords: rectal cancer; transanal endoscopic microsurgery; completion surgery; total mesorectal excision; laparoscopic surgery